Modal cutoff condition of an optical chiral fiber with different chiralities in the core and the cladding - Singh A.K.; Singh K.S.; Khastgir P.; Ojha S.P.; Singh O.N. (My University, 2025)
Electromagnetic wave propagation through a step-index optical fiber is investigated under the assumption that both the core and the cladding are made of chiral material having different chiral admittances. The characteristic modal equation is derived by the use of an exact analytical method. The cutoff conditions of such a chiral optical fiber are obtained for different special cases. The cutoff equations for a nonchiral step-index fiber are retrieved when the core and the cladding chiral admittances are set equal to zero. © 1994 Optical Society of America.